2006
DOI: 10.1007/s10237-006-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the Non-ionic Surfactant Poloxamer P188 Reduces DNA Fragmentation in Cells from Bovine Chondral Explants Exposed to Injurious Unconfined Compression

Abstract: Excessive mechanical loading to a joint has been linked with the development of post-traumatic osteoarthritis (OA). Among the suspected links between impact trauma to a joint and associated degeneration of articular cartilage is an acute reduction in chondrocyte viability. Recently, the non-ionic surfactant poloxamer 188 (P188) has been shown to reduce by approximately 50% the percentage of non-viable chondrocytes 24 h post-injury in chondral explants exposed to 25 MPa of unconfined compression. There is a que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…The concentration level was established in previous studies by this laboratory. 21,24,29 The right legs of these animals received a 1.5-mL sham injection of sterile PBS into the joint. The ''4-day no P188'' animals, received sham injections of 1.5-mL sterile PBS into both the impacted left limb and the opposite, right limb.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration level was established in previous studies by this laboratory. 21,24,29 The right legs of these animals received a 1.5-mL sham injection of sterile PBS into the joint. The ''4-day no P188'' animals, received sham injections of 1.5-mL sterile PBS into both the impacted left limb and the opposite, right limb.…”
Section: Methodsmentioning
confidence: 99%
“…There, matrix fissuring and chondrocyte death are evident post-impact [1][2][3][4][5] . Several studies have shown that chondrocytes begin to die within moments after impact and continue to die for up to several days [6][7][8][9][10] . Studies involving use of the cell-membrane-stabilizing surfactant poloxamer 188, a necrosis inhibitor, have indicated that up to 15% of chondrocytes at impact sites succumb to necrosis soon after injury 6,7,11 .…”
mentioning
confidence: 99%
“…P188 is thought to modulate cell death by stabilizing damaged cell membranes. In a recent study, P188 was shown to decrease TUNEL positive chondrocytes by 45% following 25 MPa of unconfined compression of bovine cartilage explants [4]. However, no other assays for apoptosis were employed in this study, thus precluding definitive conclusions about the effects of P188 on true apoptosis versus necrosis.…”
Section: Inhibition Of Chondrocyte Apoptosis In Vitromentioning
confidence: 93%